2011
DOI: 10.2166/wst.2011.032
|View full text |Cite
|
Sign up to set email alerts
|

One-year monthly survey of rotavirus, astrovirus and norovirus in three sewage treatment plants in Beijing, China and associated health risk assessment

Abstract: To evaluate the presence and distribution of the three main viruses (rotavirus, astrovirus, and norovirus) responsible for human acute gastroenteritis in sewerage system an one-year study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The detection frequencies for rotavirus, astrovirus, and norovirus were 48.1%, 5.6%, and 4.6%, respectively, which were in accordance with the reported frequencies of 32.3%, 6.3%, and 3.1% by rotavirus, astrovirus, and norovirus in sewerage systems (He et al 2011). The present study showed a higher prevalence of rotavirus, astrovirus, and norovirus during the cold seasons, but the difference was statistically significant only for rotavirus.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The detection frequencies for rotavirus, astrovirus, and norovirus were 48.1%, 5.6%, and 4.6%, respectively, which were in accordance with the reported frequencies of 32.3%, 6.3%, and 3.1% by rotavirus, astrovirus, and norovirus in sewerage systems (He et al 2011). The present study showed a higher prevalence of rotavirus, astrovirus, and norovirus during the cold seasons, but the difference was statistically significant only for rotavirus.…”
Section: Discussionsupporting
confidence: 88%
“…In Beijing, the treated water, regarded as a second water source, has been used as toilet flushing water, industrial process water, environmental water, garden water, and road washing water (He et al 2008). Sewage treatment and disinfective procedures for wastewater have only a limited effect on a number of viruses, and therefore treated sewage water still contain enteric viruses (Meleg et al 2006;He et al 2011). Because of discharges of treated sewage, pathogenic microorganisms may enter surface waters in Beijing, and therefore viruses are able to contam-inate environmental waters thus preserving a longterm capacity for infection.…”
Section: Introductionmentioning
confidence: 99%
“…First, the analysis of 100 effluent samples allowed us to highlight the high frequencies of detection and the high loads of HAstV, NoV GI, and NoV GII, which showed an overall consistency with the median viral loads in WWTP effluents observed worldwide, for example, 3.9 ϫ 10 4 copies per liter for HAstV, 7.1 ϫ 10 4 copies per liter for NoV GI, and 5.2 ϫ 10 4 copies per liter for NoV GII in Singapore (9), 2.9 ϫ 10 3 copies per liter for NoV GI and 2.6 ϫ 10 3 copies per liter for NoV GII in Japan (8), between 10 2 and 10 3 copies per liter for NoV GI and between 10 2 and 10 4 copies per liter for NoV GII in New Zealand (24), about 10 5 copies per liter for NoV GI and NoV GII in Norway (25), about 10 5 copies per liter for HAstV, NoV GI, and NoV GII in Germany (26), and about 10 6 copies per liter for NoV GI and NoV GII in France (27). Part of the discrepancy in the detection frequencies could be explained by the differences in the concentration and detection methods and the sample volumes used (10,11,28). Our results showed high frequencies of detection and high viral loads in the WWTP effluents, reflecting the high prevalence and high levels of circulation of human HAstV, NoV GI, and NoV GII in the human population.…”
Section: Discussionmentioning
confidence: 99%
“…A large quantity of viral particles is excreted in the feces of infected people (6,7), and they are finally circulated through the wastewater network (8,9). Viruses are generally not eliminated by wastewater treatment plants (WWTPs), and as a consequence, they can be released into rivers at noticeable levels (10)(11)(12). Consequently, we assume that the viruses in WWTP effluents could represent the viruses circulating not only in environmental waters but also in the human population.…”
mentioning
confidence: 99%
“…Several studies have reported higher frequencies of RV as compared to NoV in wastewater. Research groups from China, Tunisia and Germany described detection rates of RV ranging from 32% to 90% and NoV from 3% to 31% [26], [27], [28]. In hospital wastewater, Prado and coworkers observed RV in 95% and NoV GII in 28.5% of the samples collected between 2005 and 2008 in Rio de Janeiro, Brazil.…”
Section: Discussionmentioning
confidence: 99%